Fade dynamics analysis for for terrestrial microwave links - Zyoud, Al-Hareth; Dao, Hassan; Islam, Md. Rafiqul; Chebil, Jalel; Al-Khateeb, Khalid A. Saeed; Abd Rahman, Tharek (2010)
Terrestrial microwave system is the backbone line for mobile communication industry. In tropical region particularly in Malaysia, rain attenuation is the major constraint for implementing microwave system above 10 GHz. This paper presents statistical analysis of the dynamics of rain attenuation such as fade duration and fade slope. To prepare these statistics, rain attenuation data were obtained in Malaysia at frequencies 15 and 23 GHz for the period between January 1999 to April 2000. Fade duration statistics will be compiled for attenuation exceeding different attenuation levels (fade thresholds). The fade slope statistics will be analyzed by calculating the conditional probability density function (PDF) of fade slope for the measured data. The comparison of ITU-R models and the measured data will be investigated and analysed.